1995
DOI: 10.1172/jci117702
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced interleukin-8 release and gene expression in macrophages after exposure to Mycobacterium tuberculosis and its components.

Abstract: Mycobacterium tuberculosis infection is accompanied by acute and chronic inflammatory infiltrates associated with necrotizing granulomas in lung tissue. The cellular infiltrate is characterized by inflammatory cells which include neutrophils, lymphocytes, and macrophages. In animal and in vitro models of mycobacterial infection, cytokines including tumor necrosis factor-c (TNF-a), interferon gamma (IFNy), and interleukin-1lf participate in granulomatous inflammation. We hypothesized that interleukin-8, a pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
159
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(167 citation statements)
references
References 50 publications
6
159
2
Order By: Relevance
“…The Gro spin system defined from the 1 H-31 P HMQC spectrum (H-3/H-3Ј 3.86/3.80 ppm) (Fig. 6b) and from the HO-HAHA spectrum (H-1/H-1Ј at 4.36/4.14 ppm and H-2 at 5.12 ppm) corresponds to a diacylated Gro by reference to the standard 1,2-diacyl-3-phospho-sn-glycerol unit in Me 2 SO-d 6 : ␦ H-1/H-1Ј 4.33/4.13, ␦ H-2 5.10, ␦ H-3/H-3Ј 3.87/3.80.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The Gro spin system defined from the 1 H-31 P HMQC spectrum (H-3/H-3Ј 3.86/3.80 ppm) (Fig. 6b) and from the HO-HAHA spectrum (H-1/H-1Ј at 4.36/4.14 ppm and H-2 at 5.12 ppm) corresponds to a diacylated Gro by reference to the standard 1,2-diacyl-3-phospho-sn-glycerol unit in Me 2 SO-d 6 : ␦ H-1/H-1Ј 4.33/4.13, ␦ H-2 5.10, ␦ H-3/H-3Ј 3.87/3.80.…”
Section: Resultsmentioning
confidence: 98%
“…7a). In comparison to a standard, a L-␣-lysophosphatidylinositol dissolved in Me 2 SO-d 6 (1-acyl-2-lyso-sn-glycero-3-phospho-(1-D-myo-inositol), ␦ H-1/H-1Ј 3.99/ 3.97, ␦ H-2 3.75, ␦ H3/H3Ј 3.78/3.76), the Gro 1 H chemical shifts (Table II) indicated that the Gro was monoacylated on C1. Moreover, from the chemical shifts of the myo-Ins protons (Table II), the absence of fatty acyl appendage on the myo-Ins unit was deduced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tuberculous granulomas consist of macrophages, dendritic cells, T and B cells and fibroblasts surrounding cells infected with the bacteria and thus containing the dissemination and growth of the bacteria in the host. Production of CXCL8 during Mycobacterium tuberculosis infection modulates neutrophil and lymphocyte migration to the granuloma and high levels of CXCL8 have been associated with necrotising granulomas in infected lung tissue (Zhang et al 1995). Other chemokines, such as CXCL9, CXCL10, CCL2 and CCL5, also act in the immune response against TB.…”
mentioning
confidence: 99%
“…Lipoarabinomannans (LAMs), found ubiquitously in the genus Mycobacterium [2], represent the major antigens modulating immune responses of the host [3,4]. For example, they have been shown to regulate cytokine secretion [5][6][7][8][9][10][11][12], block the transcriptional activation of interferon-γ [13] and neutralize the potentially cytotoxic oxygen free radicals [13]. In addition, mannosylated LAMs (ManLAMs) selectively bind murine and human macrophages via the mannose receptor [14,15].…”
Section: Introductionmentioning
confidence: 99%